2018
DOI: 10.1186/s12936-018-2409-z
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of artemether–lumefantrine and dihydroartemisinin–piperaquine for the treatment of uncomplicated falciparum malaria in Muheza and Kigoma Districts, Tanzania

Abstract: BackgroundArtemether–lumefantrine (AL) is the recommended first-line artemisinin-based combination therapy (ACT) for the treatment of uncomplicated falciparum malaria in most of the malaria-endemic countries, including Tanzania. Recently, dihydroartemisinin–piperaquine (DP) has been recommended as the alternative anti-malarial to ensure effective case management in Tanzania. This study assessed the parasite clearance rate and efficacy of AL and DP among patients aged 6 months to 10 years with uncomplicated fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 38 publications
12
32
1
Order By: Relevance
“…This outcome correlate to a number of studies undertaken earlier in Kenya, Uganda, Somalia, Mali, and several other African countries indicating that Artemisinin resistance has not appeared in the African continent [19,34]. The component drug, lumefantrine, is a gradually acting drug with a long half-life time ranging from 4-7 days [48].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This outcome correlate to a number of studies undertaken earlier in Kenya, Uganda, Somalia, Mali, and several other African countries indicating that Artemisinin resistance has not appeared in the African continent [19,34]. The component drug, lumefantrine, is a gradually acting drug with a long half-life time ranging from 4-7 days [48].…”
Section: Discussionsupporting
confidence: 76%
“…In this study, AL has shown high efficacy similar to one carried in Tanzania and other parts of Africa primarily supporting the high efficacy rates of AL despite its use in the continent for over ten years [19,47]. The elevated parasite clearance rates may possibly be described by the steadfast act of artemether to clear parasites biomass leading to a quick resolution of clinical manifestation.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Immediately, resistance to SP emerged and in 2006, AL was adopted and the implementation of the new policy started in 2007 [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%